First principles : a return to humanity's shared traditions - Foy, Don, 1945- (Algora Pub., 2004)
Foy explores the differences between the foundations of modernism and traditionalism, how those differences work, and what they mean for our values and relationships: expectations within the family, how we view science, and the qualities we hold as virtues. He shows that an "updated traditional way of thinking" simply works better in some critical areas where modernism fails.